The Role of AI Leonardo, Discord, and Rytr in Business Enhancement and Digital Economic Growth in Indonesia - Ari Okta Viyani; Inna Zahara (Universitas KH. Abdul Chalim Mojokerto, 2025)
Artificial Intelligence (AI) is a series of computing techniques that can perform functions like humans. This technology can have an economic impact on a country. Unfortunately, AI adoption in Indonesia is still low and has not had an impact on the economy. Research This will explore factors that can be a driver of increasing AI adoption in Indonesia, especially in the business sector. This study will also present a comparison of 3 types of AI, namely Leonardo, discord, and Rytr. The method in study This uses a mixed method, namely qualitative and quantitative. The ZMET method is used to analyze qualitative data, and Kruskal Wallis is used for quantitative data. The results of the study show that there are several factors that can encourage the adoption of AI for business actors, one of which is the availability of an AI community, the availability of a digital incubator, and Penta helix collaboration is very necessary. The results also prove that AI Rytr has a greater influence than the 2 types of AI, Leonardo and Discord. Businesses that use AI Rytr own profit term long, availability source Power greater financial, sales growth, business image, and customer loyalty compared to 2 types of AI Leonardo and discord.